2022
DOI: 10.1021/acs.jpcb.1c08684
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Outward Proton Pumping Rhodopsin with a New Record in Thermostability by Means of Amino Acid Mutations

Abstract: We have developed a methodology for identifying further thermostabilizing mutations for an intrinsically thermostable membrane protein. The methodology comprises the following steps: (1) identifying thermostabilizing single mutations (TSSMs) for residues in the transmembrane region using our physics-based method; (2) identifying TSSMs for residues in the extracellular and intracellular regions, which are in aqueous environment, using an empirical force field FoldX; and (3) combining the TSSMs identified in ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The free‐energy function defined in our statistical‐thermodynamics theory 7,8,20–26 comprises entropic and energetic components, but the key residues are searched out using the entropic component. We define −ΔΔ S / k B as goodbreak−sans-serifΔΔsans-serif-italicS/kBgoodbreak=goodbreak−sans-serifΔsans-serif-italicS/kB()Mutantgoodbreak−{}goodbreak−sans-serifΔsans-serif-italicS/kB()WT$$ -\mathsf{\varDelta \varDelta}\mathit{\mathsf{S}}/{\mathit{\mathsf{k}}}_{\mathsf{B}}=-\mathsf{\varDelta}\mathit{\mathsf{S}}/{\mathit{\mathsf{k}}}_{\mathsf{B}}\left(\mathsf{Mutant}\right)-\left\{-\mathsf{\varDelta}\mathit{\mathsf{S}}/{\mathit{\mathsf{k}}}_{\mathsf{B}}\left(\mathsf{WT}\right)\right\} $$ where Δ S (Δ S > 0) is the gain of translational, configurational entropy of the solvent upon GPCR folding and k B is the Boltzmann constant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The free‐energy function defined in our statistical‐thermodynamics theory 7,8,20–26 comprises entropic and energetic components, but the key residues are searched out using the entropic component. We define −ΔΔ S / k B as goodbreak−sans-serifΔΔsans-serif-italicS/kBgoodbreak=goodbreak−sans-serifΔsans-serif-italicS/kB()Mutantgoodbreak−{}goodbreak−sans-serifΔsans-serif-italicS/kB()WT$$ -\mathsf{\varDelta \varDelta}\mathit{\mathsf{S}}/{\mathit{\mathsf{k}}}_{\mathsf{B}}=-\mathsf{\varDelta}\mathit{\mathsf{S}}/{\mathit{\mathsf{k}}}_{\mathsf{B}}\left(\mathsf{Mutant}\right)-\left\{-\mathsf{\varDelta}\mathit{\mathsf{S}}/{\mathit{\mathsf{k}}}_{\mathsf{B}}\left(\mathsf{WT}\right)\right\} $$ where Δ S (Δ S > 0) is the gain of translational, configurational entropy of the solvent upon GPCR folding and k B is the Boltzmann constant.…”
Section: Resultsmentioning
confidence: 99%
“…The solvent is formed by the hydrocarbon (CH 2 , CH 3 , and CH) groups constituting nonpolar chains of lipid molecules in the TM region. 7,8,[20][21][22][23][24][25][26] ΔS arises primarily from the close packing of side chains accompanying an increase in the total volume available for translational displacement of the hydrocarbon groups.…”
Section: Key Residues Searched Outmentioning
confidence: 99%
See 1 more Smart Citation
“…With only 35% sequence identity, the crystal structures are remarkably similar, but the gating residues for Cl − and Na + are located at the opposite site of the membrane ( Kato et al, 2015a ; Hosaka et al, 2016 ; Kovalev et al, 2019 ; Yun et al, 2020 ). Another example is the huge mutagenesis effort that converted a thermophilic rhodopsin into the best thermally stable rhodopsin available to date, while retaining pump activity ( Yasuda et al, 2022 ). On the other hand, selective mutations in the opsin could convert BR into an inward chloride pump, the sodium pump KR2 into a selective light-driven cation channel, the proton pumps Archaerhodopsin-3 (AR3) and Coccomyxa subellipsoidea rhodopsin (CsR) into light-driven proton channels, and the proton pump GR from Gloeobacter violaceus into a fluorescent chloride sensor ( Sasaki et al, 1995 ; Brown et al, 1996 ; Inoue et al, 2015 ; 2016 ; Fudim et al, 2019 ; Vogt et al, 2019 ; Tutol et al, 2021 ).…”
Section: Bioengineeringmentioning
confidence: 99%
“…ΔS is a solvent-entropy gain originating from an increase in the total volume available for the translational displacement of solvent particles (i.e., the hydrocarbon groups referred to above) (see Section 4.1 for more details). In our earlier studies, 10,11,[15][16][17][18][19][20][21] it was shown that ΔF/(k B T 0 ) evaluated at T = T 0 is a good measure of the GPCR thermostability. Formation of more intramolecular hydrogen bonds and closer packing of side chains lead to lower values of ΔΛ and ÀTΔS, respectively (see Sections 4.1 and 4.2).…”
Section: Introductionmentioning
confidence: 99%